Innovation in Indonesian Language Learning for Early Childhood - Haryati, Gustia (Prodi PAI STIT Sunan Giri Bima, 2025)
The purpose of this study was to determine the effectiveness of storytelling in improving the Indonesian language skills of five- to six-year-old children at Legina Kindergarten. This study employed a quantitative approach and a single-group pre-test-post-test experimental design . The study subjects were 20 children aged 5 to 6 years. Before and after the storytelling method was implemented, an Indonesian language skills test was conducted to collect data. Data were analyzed using descriptive statistics and paired-sample t-tests. The results showed that children's language skill scores increased from 59.82 in the pretest to 65.14 in the posttest. The results of the paired sample test showed a t-value of 5.23 and a significance level of 0.000 (p < 0.05). The results indicate that children's language skills differed significantly before and after the storytelling technique was used. The results show that storytelling techniques are effective in improving the Indonesian language skills of five- to six-year-old children. Therefore, storytelling techniques can be used as a relevant learning strategy to support early childhood language development in kindergarten.